LANSKAP KULISUSU DALAM TEKS LAGU DAERAH KULISUSU BUTON UTARA - William Syah; Irianto Ibrahim; La Ode Sahidin; Nur Israfyan Sofian (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to describe the Kulisusu landscape in the text of the Kulisusu North Buton regional song. This type of research is field research and the method used in this research is a descriptive method which aims to describe the research results in detail and in depth. The data used in this research is oral data from the text of the Kulisusu regional song, North Buton Regency. The data collection method is the skills method. The data collection techniques are interview techniques, recording, notes and documentation. The analytical method used is text analysis based on Michael Riffaterre's semiotics. The data analysis technique used is Michael Riffaterre's semiotics which goes through the stages of data transcription which is translated into Indonesian, data classification, Michael Riffaterre's semiotic analysis, cultural landscape analysis, data interpretation or drawing conclusions. Research data shows that there is a cultural landscape concept in every Kulisusu language regional song text from the songs Bone, Lense, Sara'ea, Alionda, and U Kolumpe Kay Mo. Contains elements of cultural landscapes such as. Landscape as a social and identity construction, cultural heritage as cultural heritage, cultural heritage as a symbol of collective values ​​and identity, cultural heritage as a representation of culture and history, cultural heritage as a means of togetherness and togetherness.